Genomic regions associated with performance in racing line of Quarter Horses - Pereira, G. L. [UNESP]; Chardulo, L. A. [UNESP]; Silva, J.A.IIV. [UNESP]; Faria, R. [UNESP]; Curi, R. A. [UNESP] (Elsevier, 2018)
Quarter Horses breed for rancing are able to run short distances faster than any other breed. Although in Brazil the effective number of animals in the racing line is relatively smaller compared to the other lines, its economic importance is substantial. Despite economic and scientific interest in this athletic trait, few efforts have been made to better understand the genetic and physiological mechanisms underlying this trait. The objective of this study was to perform genome-wide association studies (GWAS) in Quarter Horses of the racing line using equine single nucleotide polymorphism (SNP) genotyping chips for prospecting chromosome regions, genes and polymorphisms related to maximum speed index. Genotypic and phenotypic data from 305 horses genotyped with the 54 k or 65 k chip were used. Additional 187 not genotyped animal with SI record were added in the study, for a total of 492 animals and 620 horses in the pedigree used for the GWAS analysis GWAS was performed by the single-step genomic best linear unbiased prediction (ssGBLUP) method using two approaches: ssGWAS1 in which only SNP effects are recalculated at each iteration, and ssGWAS2 in which SNP effects are recalculated from updated genomic estimated breeding values (GEBVs) at each iteration. Twenty-one regions that explained more than 1% of the total genetic variance (gVar) in the maximum speed index were identified by ssGWAS1 and 12 by ssGWAS2. More than 40% of gVar was explained by these regions in ssGWAS1 and about 30% in ssGWAS2. Among chromosomes that explained more than 1% of genetic variance, five were common to both methods (equine autosomal chromosomes 3, 10, 15, 22, 25). The capacity to capture the largest number of small-effect quantitative trait loci was greater for ssGWAS1 than ssGWAS2. A total of 108 genes were identified with the first approach and 59 with the second approach. The present results show that the racing performance of Quarter Horses, given by the maximum speed index, is a quantitative trait and that no major genes exist. In general, the genes identified by enrichment analysis are related to the neuromotor system, bone and tendon development, hormonal responses, muscle contraction, and energy and sterol metabolism. These functions are considered important for the trait studied, corroborating these genes as candidates for racing performance in the Quarter Horse breed.
Keywords: Candidate gene; Enrichment analysis; Equine genotyping array; Quantitative trait loci